Technology of drilling bored piles on the difficult terrain - Osipov А.; Litnarovych, E. (Ways to Improve Construction Efficiency, 2019)
In the article on the example of the construction of a multi-storey residential complex with underground parking in the Pechersk district of Kiev, highlighted the design and technological features of the device pile foundations on the natural slope, indicates the main factors influencing the choice of technology device pile foundations on the slopes and determined the laws between the technological parameters ( at the device piles) and the level of complexity of the geotechnical conditions of the site with the slope.